Unpacking Entire Agreement Clauses: On the (Elusive) Search for Contractually Induced Formalism in Contractual Adjudication - Bertolini, Daniele (McGill Law Journal / Revue de droit de McGill, 2021)
This article examines the extent to which entire agreement clauses (EACs) are enforceable under the Canadian common law of contracts and the extent to which these contractual provisions are effective in promoting contractual certainty. EACs are generally found in commercial agreements between legally sophisticated parties and in contracts of adhesion with inequality of bargaining power between parties. Their purpose is to promote contractual certainty by establishing that the full terms of the contracts are to be found in the document containing the clause. Although the goal of EACs is to promote contractual certainty, their legal significance is far from definitive and their effectiveness is subject to several limitations. On some occasions, courts have given effect to EACs to prevent pre-contractual statements from being legally operative; in others, they have disregarded them and recognized the validity of claims based on statements external to the contract. This paper aims to examine the relevant case law relating to the enforcement of EACs and to assess the overall effectiveness of such clauses as a contractual device for promoting contractual certainty. It is suggested that courts could incrementally improve legal certainty, by more markedly differentiating the legal treatment of EACs found in fully negotiated contracts between sophisticated parties and contracts of adhesion.